Faktor penghambat pemasaran UMKM pada sektor makanan di Provinsi Banten (Studi kasus: Kota Cilegon) - Ayyub, Dery; Prima, Ongko; Cahya, Riky Dwi; Wijaya, Said Hadi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to identify factors inhibiting MSME marketing in the food sector in Cilegon City. The method used consists of a quantitative survey involving 100 MSME players and in-depth interviews with 10 selected MSME players. The results show that limited capital, low marketing knowledge, limited use of technology, and narrow market access are the main constraints. In addition, complicated government regulations also exacerbate marketing barriers. Most MSME players still rely on traditional marketing methods and need support in digital marketing and ease of business licensing. This study suggests that the government provide greater training and support to accelerate the growth of MSMEs in the food sector.